Evaluating the effects of changing global climate on amphibian functional groups of southern Africa: an ecophysiology modelling approach - Mokhatla, Mohlamatsane McDonald (Stellenbosch : Stellenbosch Univesity, 2018)
Thesis (PhD)--Stellenbosch University, 2018.